The Role of Employees' Innovative Work in Mediation of The Influence of Transformational Leadership on Performance Improvement - Panji Anom, Sendika; Gustomo, Aurik (Riviera Publishing, 2023)
The results of PT Gapura Angkasa's 2018-2020 Employee Satisfaction Survey measurements show that the Relationship Variable with direct superiors is the indicator with the lowest level of satisfaction and has a high level of importance for three consecutive years. This study aims to analyze leadership factors in a company that are very important in encouraging employee creativity and innovation to achieve the desired goals or work results. The purpose of this study was to determine the effect of transformational leadership on employee performance which is mediated by the innovative work behavior of employees of PT Gapura Angkasa, and how it influences one another. Quantitative methods were used to collect data by distributing questionnaires and processing the data using the Structural Equation Model with Smart PLS software to test the hypothesis. These results were then deepened to find out the extent of Transformational Leadership practices in the company by conducting interviews with six respondents. The results of this study will show a positive and significant relationship between transformational leadership on innovative work behavior, transformational leadership on employee performance, and the relationship between transformational leadership on employee performance mediated by creative work behavior. Then the results of deepening related to Transformational leadership practices in companies found priority improvements in the Transformational Leadership dimension, namely the Intellectual Stimulation variable. Efforts to increase transformational leadership based on the results of qualitative data are fostering a culture of innovation, enabling employees to embody new ideas, and providing space for employees to innovate and explore creativity.